2008
DOI: 10.4103/0970-0218.40875
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance among nosocomial isolates in a teaching hospital in Goa

Abstract: Background:Emergence of polyantimicrobial resistant strains of hospital pathogens has presented a challenge in the provision of good quality in-patient care. Inappropriate use of antibiotics in the hospital is largely responsible for this catastrophe. Bacteriological surveillance of the cases of nosocomial infections is crucial for framing an evidence-based antimicrobial policy for a hospital.Materials and Methods:A prospective study was undertaken among 498 patients from medicine and surgery wards in a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 8 publications
8
30
0
Order By: Relevance
“…The result of this study is in agreement with previous studies. 9,11 Our findings confirm the results of another study from northern India. Agarwal et al found majority of infections with gramnegative bacilli in respiratory ICU.…”
Section: Discussionsupporting
confidence: 90%
“…The result of this study is in agreement with previous studies. 9,11 Our findings confirm the results of another study from northern India. Agarwal et al found majority of infections with gramnegative bacilli in respiratory ICU.…”
Section: Discussionsupporting
confidence: 90%
“…Surgical site infection is an important outcome indicator after surgery. The situation is worsened by the emergence of polymicrobial resistant strains of nosocomial pathogens [5]. The infection rate in the present study was 24.2% including postdischarge surveillance and compares favorably with other reported rates ranging from 2.5 to 41.9% [6][7][8][9][10].…”
Section: Discussionsupporting
confidence: 76%
“…The incidence of NI was higher among the patients of medical (28%) ward than surgical (24.5%) ward, however, the difference was statistically insignificant (p=0.58). Similar finding was seen by Kamat et al, [11], which is higher than the previous studies in which Infection rate were 16.4% [12] and 13% [13] and lower than following studies where NI rate was 27.4% [14].…”
Section: References Discussionsupporting
confidence: 36%